A Guide to Creative Engagement in Public Spaces - Victoria Foster (21491630) (2025)
This co-created guide is a resource aimed at community groups and others who would like to engage in civic activities aimed at building understanding and connections in their localities. It details an innovative approach to engaging the general public in creative, meaningful conversations using co-created poetry.